2017
DOI: 10.1002/jcb.26285
|View full text |Cite
|
Sign up to set email alerts
|

Human biliverdin reductase regulates the molecular mechanism underlying cancer development

Abstract: Human biliverdin reductase (hBVR), is an enzyme, that converts biliverdin to bilirubin, and has been implicated in epithelial-mesenchymal transition (EMT) in breast cancer. However, few studies have investigated the role of hBVR in cell apoptosis in other cancers. Therefore, the aim of this study was to investigate the effects of hBVR in several lines of cancer cells. The results of this study showed that hBVR expression was up-regulated in breast, lung, and liver cancers, but not ovarian cancer. Moreover, hBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Results collected in the current study further strengthen the role of IL-8 and Caspase-3 in VAT dysfunction, by providing a potential mechanism associated with BVR-A and leading to their elevation. Indeed, as previously reported, BVR-A silencing leads to a significant increase of Caspase-3 levels in different cell types [35] whereas biliverdin administration significantly decreased the LPS-mediated IL-8 gene expression and secretion [36] thus supporting a role for BVR-A in controlling the inflammatory response [37]. In particular, the role of IL-8 and Caspase-3 in VAT inflammation was highlighted by several studies.…”
Section: Discussionmentioning
confidence: 52%
“…Results collected in the current study further strengthen the role of IL-8 and Caspase-3 in VAT dysfunction, by providing a potential mechanism associated with BVR-A and leading to their elevation. Indeed, as previously reported, BVR-A silencing leads to a significant increase of Caspase-3 levels in different cell types [35] whereas biliverdin administration significantly decreased the LPS-mediated IL-8 gene expression and secretion [36] thus supporting a role for BVR-A in controlling the inflammatory response [37]. In particular, the role of IL-8 and Caspase-3 in VAT inflammation was highlighted by several studies.…”
Section: Discussionmentioning
confidence: 52%
“…Apart from being used as a novel biomarker for nasopharyngeal carcinoma [45], UCB has the potential to cause cell cycle arrest at G0/G1 and exert pro-oxidant effects at high concentrations [46]. Human biliverdin reductase, which chemically reduces biliverdin to bilirubin, was recently implicated as a regulator in cancer development and maybe useful in designing biomarkers for cancer patients [47]. A similar study reported that lower serum bilirubin levels occur in colorectal cancer patients with a 1µM decrease in serum bilirubin related to a 7% rise in CRC risk [48].…”
Section: Discussionmentioning
confidence: 99%
“…Also, BLVRA, another important enzyme in the heme catabolic pathway, has been proposed as promoting carcinogenesis [ 18 ]. In fact, the increased expression of BLVRA has been demonstrated in patients with hepatocellular cancer [ 19 ], as well as in breast and lung cancer cell lines [ 20 ]. Nevertheless, in our in vitro studies on human pancreatic cancer cells, we did not observe any effects of chlorophylls on BLVRA expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been proposed that BLVRA plays a role in the promotion of carcinogenesis [ 18 ]. In fact, increased BLVRA expression has been observed in patients with hepatocellular cancer [ 19 ] and in breast and lung cancer cell lines [ 20 ].…”
Section: Introductionmentioning
confidence: 99%